2018
DOI: 10.1038/s41419-018-1022-y
|View full text |Cite
|
Sign up to set email alerts
|

Distinct multilevel misregulations of Parkin and PINK1 revealed in cell and animal models of TDP-43 proteinopathy

Abstract: Parkin and PINK1 play an important role in mitochondrial quality control, whose malfunction may also be involved in the pathogenesis of amyotrophic lateral sclerosis (ALS). Excessive TDP-43 accumulation is a pathological hallmark of ALS and is associated with Parkin protein reduction in spinal cord neurons from sporadic ALS patients. In this study, we reveal that Parkin and PINK1 are differentially misregulated in TDP-43 proteinopathy at RNA and protein levels. Using knock-in flies, mouse primary neurons, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…TDP-43 was found to govern Parkin mRNA levels in both an intron-mediated and intron-independent manner. While TDP-43 did not regulate Pink1 at the RNA level, its overexpression led to the cytosolic accumulation of cleaved PINK1 due to the impairment of the ubiquitin–proteasome system [ 46 ]. In stress conditions, such as ageing, this accumulation of cleaved PINK1 leading to reduced mitochondrial activity may be a risk factor promoting neurodegeneration.…”
Section: Pink1/parkin In Neurodegenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…TDP-43 was found to govern Parkin mRNA levels in both an intron-mediated and intron-independent manner. While TDP-43 did not regulate Pink1 at the RNA level, its overexpression led to the cytosolic accumulation of cleaved PINK1 due to the impairment of the ubiquitin–proteasome system [ 46 ]. In stress conditions, such as ageing, this accumulation of cleaved PINK1 leading to reduced mitochondrial activity may be a risk factor promoting neurodegeneration.…”
Section: Pink1/parkin In Neurodegenerationmentioning
confidence: 99%
“…In stress conditions, such as ageing, this accumulation of cleaved PINK1 leading to reduced mitochondrial activity may be a risk factor promoting neurodegeneration. Lastly, Sun et al [ 46 ] found that by ameliorating the misregulation of PINK1 or PARKIN by their down or up-regulation, respectively, leads to suppression of the degenerative phenotypes observed in a TDP-43 proteinopathy fly model.…”
Section: Pink1/parkin In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopaminergic overexpression of parkin or PINK1 prevents the loss of DA neurons and rescues climbing defects in the PARIS transgenic flies ( Fig. 3a-d, Additional file 9, Targeted knockdown of either parkin or PINK1 using specific shRNA lines [48][49][50] in the DA neurons leads to loss of DA neurons and climbing defects and further exacerbates these dopaminergic phenotypes in the PARIS overexpressing flies ( Fig. 3a-d Figure S2 and Additional file 13, Figure S3 Immunoblot analysis reveals that dopaminergic knockdown of parkin or PINK1 leads to marked accumulation of PARIS whereas PARIS levels are significantly decreased in flies overexpressing parkin or PINK1 (Fig.…”
Section: Parkin Pink1 and Pgc-1α Rescue Dopaminergic Neuron Loss Caumentioning
confidence: 99%
“…Nevertheless, CHCHD10 S59L expression induced PINK1 stabilization in mitochondria without strong disruption of mitochondrial membrane potential, and genetic/pharmacologic inhibition of PINK1 mitigated CHCHD10 S59L -induced toxicity. Reducing PINK1 or parkin-mediated pathways are beneficial in in vivo disease models of SOD1, FUS, and TARDBP mutations (55)(56)(57). We demonstrated that MFN2 agonists enhanced ATP production in flies expressing C9ORF72 with GGGGCC repeats.…”
Section: Discussionmentioning
confidence: 80%